German-Jewish thought and its afterlife a tenuous legacy - Liska, Vivian 1956- (Indiana University Press, 2017)
"The visions of modernity depicted in the writings of major Modernist German-Jewish writers and philosophers manifest, says Vivian Liska, the paradoxical dynamic that the break with tradition invokes figures of thought derived from Jewish tradition. In German-Jewish Thought and Its Afterlife, Liska innovatively focuses on the changing form, fate and function of messianism, law, exile, election, remembrance, and the transmission of tradition itself in three different temporal and intellectual frameworks: German-Jewish modernism, postmodernism, and the current period. Highlighting these elements of the Jewish tradition in the works of Franz Kafka, Walter Benjamin, Gershom Scholem, Hannah Arendt, and Paul Celan, Liska reflects on dialogues and conversations between them and on the reception of their work. She shows how this Jewish dimension of their writings is transformed, but remains significant in the theories of Maurice Blanchot and Jacques Derrida and how it is appropriated, dismissed or denied by some of the most acclaimed thinkers at the turn of the twenty-first century such as Giorgio Agamben, Slavoj Žižek, and Alain Badiou."...
Includes bibliographical references (pages 169-198) and index
Keywords: Geschichte 1920-1980; Juden; Jews -- Germany -- Intellectual life; Jews -- Germany -- Civilization; Jüdische Literatur; Jüdische Philosophie; Deutschland